The Impact of the COVID-19 Epidemic During the Lockdown on Children With the Pediatric Acute-Onset Neuropsychiatric Syndrome (PANDAS/PANS): The Importance of Environmental Factors on Clinical Conditions - Guido, Cristiana Alessia; Loffredo, Lorenzo; Zicari, Anna Maria; Pavone, Piero; Savasta, Salvatore; Gagliano, Antonella; Brindisi, Giulia; Galardini, Giuliana; Bertolini, Antonella; Spalice, Alberto (Frontiers in Neurology, 2021)
In March 2020, SARS-CoV-2 declared a pandemic by the World Health Organization (WHO, 2020). Restrictive isolation measures have also brought psychological distress to the pediatric population. Building on the syndrome's characteristics, the present study explored the impact of lockdown on the clinical course of young people with PANDAS / PANS. The initial hypothesis considered both the reduced exposure to viral agents and the strategies of the parents and other containment actions as protective factors against the worsening of symptoms. Methods: 108 children, adolescents, and young adults were recruited according to the multicenter PANDAS/PANS research program. Parents participated in a web-based survey. Results: contrary to our hypothesis, the study results show an increase in symptoms during the block in 71% of the sample. Psychometric analyzes allowed us to exclude a relationship between the main symptoms of PANDAS and the increase in symptoms or the presence of symptoms before the block and their increase over time. The increase in symptoms is best explained by the presence of sleep disturbances and emotional lability. The exacerbation also appears to be linked to the onset of new symptoms in children and adolescents with depressed moods and eating problems. Furthermore, irritability and oppositionality are significant predictors of acute exacerbation. E Conclusion: This preliminary study highlights the importance of studying the causes of increased symptoms in children with PANDAS / PANS. Life events can exacerbate the clinical condition or generate new symptoms in young patients. In particular, environmental, family, and social changes in the course of clinical symptoms in PANDAS / PANS patients should be investigated. It highlights the importance of emotional and behavioral management, which can be improved by enhancing coping strategies in young people with PANDAS / PANS and their caregivers through a combination treatment in which CBT and PMT are included, in line with guidelines.